A nomogram to predict distant metastasis after neoadjuvant chemoradiotherapy and radical surgery in patients with locally advanced rectal cancer. Issue 4 (20th January 2017) - Sun, Yanwu; Lin, Huiming; Lu, Xingrong; Huang, Ying; Xu, Zongbin; Huang, Shenghui; Wang, Xiaojie; Chi, Pan
Abstract : PURPOSE: To compare distant metastasis (DM) in locally advanced rectal cancer (LARC) patients treated with neoadjuvant chemoradiotherapy (nCRT) and surgery alone, and to develop a predictive nomogram for DM following nCRT. METHODS: Propensity‐scoring match analysis was performed to compare DM in LARC treated with nCRT ( n = 375) and surgery alone ( n = 375). Cox regression was performed to identify predictors of DM following nCRT. A nomogram was developed and validated by internal ( n = 425) and external validation ( n = 97). RESULTS: The 5‐year local recurrence rate was significantly lower in the nCRT group (5.6% vs. 10.4%; P = 0.020). The 5‐year DM rates (nCRT vs. surgery alone: 25.3% vs. 24.4%; P = 0.235) were similar between groups. Cox regression showed that the post‐nCRT pathologic stage (ypTNM stage, OR = 2.022, P = 0.002), IMA nodal metastasis ( OR = 2.171, P = 0.023), and CRM involvement ( OR = 2.535, P = 0.016) were independently associated with DM following nCRT. A predictive nomogram was developed with a C‐index of 0.70 on internal validation, and 0.71 on the external validation. CONCLUSION: NCRT improved local control, but not distant metastasis. A nomogram to predict 3‐ and 5‐year DM rates, using clinicopathological parameters, was successfully developed. This prognostic tool could support decision‐making in clinical practice and follow‐up strategies.